2022
DOI: 10.1109/tvcg.2022.3209477
|View full text |Cite
|
Sign up to set email alerts
|

LargeNetVis: Visual Exploration of Large Temporal Networks Based On Community Taxonomies

Abstract: Fig. 1. LargeNetVis is a web-based visual analytics system designed to support the visual exploration of temporal networks with up to a few thousand nodes and timestamps. The system is composed of four linked visual components. While the Taxonomy Matrix (A) and Global View (B) enable global-level analysis, the node-link diagram (C) and the Temporal Activity Map (D) enable structural and temporal local-level analysis, respectively. The system also provides a panel with the network, community, or node numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Workarounds: Before discussing workarounds, we would like to make clarification on the definition of "large" in our context. There are different definitions for "large-scale", ranging from 50 nodes [56] to thousands of nodes [57] and even to millions of nodes [58]. These variations account for differences in the domain, the data itself, tasks and visual techniques [56].…”
Section: Discussionmentioning
confidence: 99%
“…Workarounds: Before discussing workarounds, we would like to make clarification on the definition of "large" in our context. There are different definitions for "large-scale", ranging from 50 nodes [56] to thousands of nodes [57] and even to millions of nodes [58]. These variations account for differences in the domain, the data itself, tasks and visual techniques [56].…”
Section: Discussionmentioning
confidence: 99%
“…To do that, we took advantage of a dataset with market basket information that we modeled as temporal networks focused on purchases of products from the perspective of three distinct groups of household customers, characterized by their annual income. Using LargeNetVis [Linhares et al 2023], an interactive system with layouts and features to analyze small and large temporal networks, we then performed a series of exploratory analyses that allowed us to inspect structure (identifying, e.g., purchase patterns and relations between items and users' preferences) and temporal dynamics (e.g., purchases trends and seasonalities).…”
Section: Discussionmentioning
confidence: 99%
“…We have considered different interactive systems for visualizing temporal networks (e.g., DyNetVis [Linhares et al 2020] and PaohVis [Valdivia et al 2021]). After an initial investigation, we chose LargeNetVis [Linhares et al 2023] because it enables effective analyses of temporal aspects and also can handle temporal networks with a few thousand nodes and edges, such as the ones described in Tab. 1, which would be difficult or infeasible with other systems.…”
Section: Visual Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An important question in the context of an experiment like ours is how well the results may scale to larger or more complex networks. There is no clear definition of the number of nodes above which a network is considered to be large (see, e.g., [89]). While for some applications, large networks may refer to thousands or even millions of nodes, Yoghourdjian et al surveyed empirical network visualisation studies and found that such sizes were underrepresented among these studies.…”
Section: Limitationsmentioning
confidence: 99%